Film and Slide Show Media Education in Improving Students Knowledge and Attitudes About Drugs at SMUN 1 Peureulak - Meutia; Kintoko Rochadi; Edy Syahrial (International Archives of Medical Sciences and Public Health, 2021)
Introduction: Narcotics are substances that, when injected into thebody, produce a specific effect on the user, such as anaesthesia, painrelief, spiritual stimulation, and hallucinations, or they can causedelusions. This is a quasi-experimental or quasi-experimental studyto determine the effectiveness of Extension Through Media Film AndSlide Show To Increased Students' Knowledge and Attitude TowardsDrug Abuse in SMU 1 Peureulak, East Aceh, 2015. Method: Thepopulation of the study consisted of all 918 students of SMAN 1Peureulak, with a total sample size of 60 students divided into twogroups: 30 students who received counseling via film and 30 studentswho received counseling via slide show. From November 2014 toMay 2015, this study was conducted. Pre- and post-testquestionnaires were used to collect data, which were analyzed usingthe uji wilcoxon test at a 95% confidence level. Result : The analysisrevealed that drug counseling had an effect on knowledge with a pvalue of 0.001 in the film medium and p value of 0.001 in the mediaslide show, as well as on attitude with a p value of 0.001 in the filmmedium and p value of 0.001 in the media slide show. The findingsindicated that there is a difference in students' knowledge (p = 0.005)and attitude (p = 0.630) after receiving counseling via film and slideshow. Conlusion I was recommended to the school to educatestudents about drugs through the learning process and to becomeactively involved in researching and disseminating information aboutdrugs through the medium of film.